De novo frameshift mutation in ASXL3 in a patient with global developmental delay, microcephaly, and craniofacial anomalies - Dinwiddie, Darrell L (BioMed Central, 2013)
BACKGROUND: Currently, diagnosis of affected individuals with rare genetic disorders can be lengthy and costly, resulting in a diagnostic odyssey and in many patients a definitive molecular diagnosis is never achieved despite extensive clinical investigation. The recent advent and use of genomic medicine has resulted in a paradigm shift in the clinical molecular genetics of rare diseases and has provided insight into the causes of numerous rare genetic conditions. In particular, whole exome and genome sequencing of families has been particularly useful in discovering de novo germline mutations as the cause of both rare diseases and complex disorders. CASE PRESENTATION: We present a six year old, nonverbal African American female with microcephaly, autism, global developmental delay, and metopic craniosynostosis. Exome sequencing of the patient and her two parents revealed a heterozygous two base pair de novo deletion, c.1897_1898delCA, p.Gln633ValfsX13 in ASXL3, predicted to result in a frameshift at codon 633 with substitution of a valine for a glutamine and introduction of a premature stop codon. CONCLUSIONS: We provide additional evidence that, truncating and frameshifting mutations in the ASXL3 gene are the cause of a newly recognized disorder characterized by severe global developmental delay, short stature, microcephaly, and craniofacial anomalies. Furthermore, we expand the knowledge about disease causing mutations and the genotype-phenotype relationships in ASXL3 and provide evidence that rare, nonsynonymous, damaging mutations are not associated with developmental delay or microcephaly.